2013
DOI: 10.1371/journal.pntd.0002362
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia-Associated Bacterial Protection in the Mosquito Aedes aegypti

Abstract: Background Wolbachia infections confer protection for their insect hosts against a range of pathogens including bacteria, viruses, nematodes and the malaria parasite. A single mechanism that might explain this broad-based pathogen protection is immune priming, in which the presence of the symbiont upregulates the basal immune response, preparing the insect to defend against subsequent pathogen infection. A study that compared natural Wolbachia infections in Drosophila melanogaster with the mosquito vector Aede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
92
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 71 publications
5
92
1
1
Order By: Relevance
“…We observed that wAlbB protects WB1 mosquitoes from all three types of pathogen. This is in agreement with a previous report showing that both wMel and wMelPop can protect A. aegypti from infection with Gram-negative bacteria (Erwinia carotovora and Salmonella typhimurium), and wMelPop can increase survival of mosquitoes after challenge with Gram-positive bacteria (Mycobacterium marinum) (Ye et al, 2013). Thus, Wolbachiaboosted immunity is beneficial to the mosquito host owing to Wolbachia-associated protection against pathogens.…”
Section: Discussionsupporting
confidence: 93%
“…We observed that wAlbB protects WB1 mosquitoes from all three types of pathogen. This is in agreement with a previous report showing that both wMel and wMelPop can protect A. aegypti from infection with Gram-negative bacteria (Erwinia carotovora and Salmonella typhimurium), and wMelPop can increase survival of mosquitoes after challenge with Gram-positive bacteria (Mycobacterium marinum) (Ye et al, 2013). Thus, Wolbachiaboosted immunity is beneficial to the mosquito host owing to Wolbachia-associated protection against pathogens.…”
Section: Discussionsupporting
confidence: 93%
“…[36][37][38][39][40] With the growing realization of the diversity of the mosquito microbiome, it is important to understand the nature of these microorganisms and the role they may play in vector ecology and arbovirus transmission. Few studies have been done to evaluate potential interactions between insectspecific viruses with arboviruses in mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…This broad-spectrum pathogen protection happens through immune priming that upregulates the basal immune response by inducing an array of reactions like cytoplasmic incompatibility (CI) in the presence of the symbiont and better preparing insects against subsequent infection by pathogens [30]. The similar kind of observation was found in transient infections established in the mosquito Anopheles gambiae [30,31]. Biocontrol strategy for reducing dengue virus transmission to humans may be achieved in future through the Wolbachia symbiont-infected mosquitoes [25].…”
Section: Diversity and Role Of Insect Gut Microbes And Their Environmmentioning
confidence: 89%
“…It is also reported that when Plasmodium gallinaceum, a malaria parasite is stably transfected into Aedes aegypti mosquitoes, protection against the parasite is conferred [28,29]. This broad-spectrum pathogen protection happens through immune priming that upregulates the basal immune response by inducing an array of reactions like cytoplasmic incompatibility (CI) in the presence of the symbiont and better preparing insects against subsequent infection by pathogens [30]. The similar kind of observation was found in transient infections established in the mosquito Anopheles gambiae [30,31].…”
Section: Diversity and Role Of Insect Gut Microbes And Their Environmmentioning
confidence: 99%
See 1 more Smart Citation